Changes in dissolved organic matter (DOM) amount and composition along nested headwater stream locations during baseflow and stormflow. Issue 6 (1st August 2014) - Singh, Shatrughan; Inamdar, Shreeram; Mitchell, Myron
Abstract Amount and composition of dissolved organic matter (DOM) were evaluated for multiple, nested stream locations in a forested watershed to investigate the role of hydrologic flow paths, wetlands and drainage scale. Sampling was performed over a 4‐year period (2008–2011) for five locations with drainage areas of 0.62, 3.5, 4.5, 12 and 79 ha. Hydrologic flow paths were characterized using an end‐member mixing model. DOM composition was determined using a suite of spectrofluorometric indices and a site‐specific parallel factor analysis model. Dissolved organic carbon (DOC), humic‐like DOM and fluorescence index were most sensitive to changes with drainage scale, whereas dissolved organic nitrogen, specific UV absorbance, Sr and protein‐like DOM were least sensitive. DOM concentrations and humic‐like DOM constituents were highest during both baseflow and stormflow for a 3.5‐ha catchment with a wetland near the catchment outlet. Whereas storm‐event concentrations of DOC and humic DOM constituents declined, the mass exports of DOC increased with increasing catchment scale. A pronounced dilution in storm‐event DOC concentration was observed at peak stream discharge for the 12‐ha drainage location, which was not as apparent at the 79‐ha scale, suggesting key differences in supply and transport of DOM. Our observations indicate that hydrologic flow paths, especially during storms, and the location and extent of wetlands in the catchment are key determinants of DOM concentration and composition. This study furthers our understanding of changes in DOM with drainage scale and the controls on DOM in headwater, forested catchments. Copyright © 2014 John Wiley & Sons, Ltd.